Metabolic syndrome, social isolation, and sarcopenia in mild cognitive impairment: A multifaceted analysis of risk factors and mediating pathways - Shuang Deng; Zhongqiang Guo; Min Liu (PLoS ONE, 2025)
Background Metabolic syndrome (MetS), social isolation (SI), and sarcopenia are potential modifiable risk factors for mild cognitive impairment (MCI); however, the interactions among these factors and their mediating mechanisms remain unclear. Method This study utilized data from the China Health and Retirement Longitudinal Study (CHARLS 2015), which included 2,637 subjects aged 45 and older. We employed multivariate logistic regression, a threshold effect model, bootstrap mediation analysis, and stratified analysis to investigate the associations and mechanisms between metabolic syndrome (MetS), the visceral adiposity index (VAI), the atherogenic index of plasma (AIP), nonhigh-density lipoprotein cholesterol (NHDL), social isolation (SI), accessory skeletal muscle mass (ASM), and mild cognitive impairment (MCI). Results Independent effects such as social isolation (OR=1.397, 95% CI = 1.091–1.789), METS_IR (OR=0.976/unit), AIP (OR=0.593), and low ASM (OR=0.903/unit) were significantly correlated with MCI (all P < 0.05). The threshold effect indicates that there is a turning point for METS_IR at 27.75. The risk reduction was more pronounced when it was less than 27.752 (OR=0.905 vs. 0.982, P = 0.002). Mediating pathways: AIP and NHDL mediate 21.9% and 19.7% of the effects of METS_IR on MCI, respectively; social isolation mediated 3.9% of the effects of ASM (all P < 0.05). Population differences: The protective effect of AIP was more significant among females (OR=0.512), in rural areas (OR = 0.350), and in populations with low education (OR=0.565) (P < 0.05). Conclusion Metabolic disorders, social isolation, and sarcopenia increase the risk of MCI through independent and synergistic effects, which are partially mediated by lipid metabolism pathways. A multidimensional strategy integrating metabolic management, social support, and muscle strength intervention needs to be developed for high-risk populations such as elderly individuals and rural women.